PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING TERHADAP MOTIVASI BELAJAR SISWA: e-learning - Jenivia Anggi Afriandini; Anjeli; Detri Amelia Chandra; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the impact of using e-learning instructional media on students' learning motivation through a qualitative approach using literature review. The data were collected from various secondary sources such as scientific journal articles, books, and previous research reports. The analysis shows that the use of e-learning-based instructional media contributes positively to enhancing students’ motivation to learn. E-learning is considered capable of creating a more interactive and flexible learning environment that aligns with individual learning styles. These findings highlight that the integration of technology in education can significantly increase students’ engagement and motivation.